2021
DOI: 10.1001/jamaoncol.2020.5745
|View full text |Cite
|
Sign up to set email alerts
|

Serial Screening for COVID-19 in Asymptomatic Patients Receiving Anticancer Therapy in the United Arab Emirates

Abstract: Patients with cancer, especially those receiving anticancer therapy, are at risk amidst the coronavirus disease 2019 (COVID-19) pandemic. 1-3 Given the frequency of asymptomatic COVID-19, 2,4,5 and presymptomatic transmission, 5 symptombased screening may inadequately triage patients to safely resume anticancer therapy. 2,6 We thus implemented a pilot microbiologic screening program in Al Zahra Hospital in the United Arab Emirates (UAE), identifying presymptomatic COVID-19 in nearly 1 in 10 patients with cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
0
15
1
1
Order By: Relevance
“…These studies included a total of 104,058 laboratory-confirmed COVID-19 cases, of which 25,050 exhibited no symptoms at the time of testing and 7,220 remained asymptomatic. We identified 170 studies that reported asymptomatic infections ( 11 13 , 17 183 ), 332 studies that reported silent infections at the time of testing ( 10 12 , 14 , 17 20 , 23 27 , 31 , 32 , 35 40 , 42 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 58 , 60 66 , 68 , 69 , 73 75 , 77 79 , 81 , 84 , 87 , 90 94 , 97 , 99 , 101 , 103 , 104 , 106 , 111 , 113 116 , 118 , 119 , 121 123 , 125 , 127 , 128 , …”
Section: Resultsmentioning
confidence: 99%
“…These studies included a total of 104,058 laboratory-confirmed COVID-19 cases, of which 25,050 exhibited no symptoms at the time of testing and 7,220 remained asymptomatic. We identified 170 studies that reported asymptomatic infections ( 11 13 , 17 183 ), 332 studies that reported silent infections at the time of testing ( 10 12 , 14 , 17 20 , 23 27 , 31 , 32 , 35 40 , 42 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 58 , 60 66 , 68 , 69 , 73 75 , 77 79 , 81 , 84 , 87 , 90 94 , 97 , 99 , 101 , 103 , 104 , 106 , 111 , 113 116 , 118 , 119 , 121 123 , 125 , 127 , 128 , …”
Section: Resultsmentioning
confidence: 99%
“…However, we were able to classify malignancies in clinically relevant categories, i.e., haematological cancers, non-haematological cancers, skin melanoma, and other types of cancers. The classification was not based on clinical characteristics; rather it was based on the number of positive COVID-19 cases per each distinct cancer type (it had to be >20 diagnosed cases).Finally, we assume that controls that were not tested for COVID-19 do not develop the disease which may have induced a selection bias because some of the cancer patients might be asymptomatic [43]. We argue that given their cancer status the majority of control patients developing symptoms compatible with COVID-19 they would have been tested, also we have performed sensitivity analyses demonstrating consistency of results even if non-tested patients were excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific societies and health policy makers have emphasized the value of screening cancer patients under active treatment [ 7 , 12 ], but screening intensity is a matter of debate, taking into consideration available resources and potential delays. A recent study evaluated the role of performing sequential molecular testing for SARS-CoV-2 in both cancer patients and health care professionals [ 13 ]. Cancer patients under intravenous therapies were tested prior to each cycle of therapy, and site staff were tested at regular intervals.…”
Section: Discussionmentioning
confidence: 99%